IMPLEMENTASI PERATURAN PRESIDEN NOMOR 26 TAHUN 2009 TENTANG KEBIJAKAN PELAYANAN e-KTP PADA KANTOR KECAMATAN DI WILAYAH KOTA BANJARBARU - Widiati (stiatabalong.ac.id, 2024)
The E-KTP programme was initiated in response to the conventional ID card system in Indonesia, which allowed individuals to possess more than one ID card. The policy for changing the administration of population registration, as mandated by Law Number 23 of 2006, aims to establish an orderly population database, proper issuance of Population Identification Numbers (NIK), and accurate population documents. To achieve the main goals of population administration, it is necessary to implement a Nationally-based NIK ID card (Electronic ID Card) for all eligible residents. This study aims to examine the implementation of Presidential Regulation Number 26 of 2009 concerning the E-KTP service policy in sub-districts within Banjarbaru City, focusing on the challenges encountered and possible solutions. The research was conducted using a qualitative method, with data collected through interviews, documentation, and field observations. Primary data sources included informants, supported by observations and documentation from the research location. The data analysis was conducted using qualitative descriptive techniques. The study's findings reveal that the implementation of Presidential Regulation Number 26 of 2009 regarding the E-KTP service policy at sub-district offices in Banjarbaru City has been effective, with clear procedures and free services. However, challenges remain, including residents who are registered but have not yet completed the E-KTP recording, a shortage of service staff or operators (only one person available), and a lack of information and socialisation regarding E-KTP knowledge among the local population. The implications of this research suggest the need to raise public awareness about the importance of the E-KTP programme, increase the number of service staff or operators, and enhance the dissemination of information and socialisation efforts related to E-KTP awareness among the community. Keywords: Evaluation, Implementation, E-KTP